Systematic review and meta‐analysis of intravenous iron‐carbohydrate complexes in HFrEF patients with iron deficiency - Andrew Sindone; Wolfram Doehner; Josep Comin‐Colet (ESC Heart Failure, 2023)
Abstract Iron deficiency (ID) is a common co‐morbidity in patients with heart failure (HF). The present meta‐analysis evaluates the effect of intravenous (IV) iron‐carbohydrate complex supplementation in patients with HF with reduced ejection fraction (HFrEF) and ID/iron deficiency anaemia (IDA). Randomized controlled trials (RCTs) comparing IV iron‐carbohydrate complexes with placebo/standard of care in patients with HFrEF with ID/IDA were identified using Embase (from 1957) and PubMed (from 1989) databases through 25 May 2021. Twelve RCTs including 2381 patients were included in this analysis. The majority (90.8%) of patients receiving IV iron‐carbohydrate therapy were administered ferric carboxymaltose (FCM); 7.5% received iron sucrose and 1.6% received iron isomaltoside. IV iron‐carbohydrate therapy significantly reduced hospitalization for worsening HF [0.53 (0.42–0.65); P < 0.0001] and first hospitalization for worsening HF or death [0.75 (0.59–0.95); P = 0.016], but did not significantly impact all‐cause mortality, compared with control. IV iron‐carbohydrate therapy significantly improved functional and exercise capacity compared with the control. There was no significant difference in outcome between IV iron‐carbohydrate formulations when similar endpoints were measured. No significant difference in adverse events (AE) was observed between the treatment groups. IV iron‐carbohydrate therapy resulted in improvements in a range of clinical outcomes and increased functional and exercise capacity, whereas AEs were not significantly different between IV iron‐carbohydrate and placebo/standard of care arms. These findings align with the European Society of Cardiology's 2021 HF guidelines, which recommend the consideration of FCM in symptomatic patients with a left ventricular ejection fraction < 45% and ID.